2017
DOI: 10.1007/s13187-017-1314-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Pain Management at Oncology Units: Comparing Knowledge, Attitudes and Perceived Barriers Between Physicians and Nurses

Abstract: Pain is a major symptom that causes suffering among patients diagnosed with cancer. Identifying physicians' and nurses' knowledge, attitudes, and their perceived barriers of cancer pain management is considered an essential step in improving cancer pain relief. The purposes of this study are to compare physicians' and nurses' knowledge and attitudes toward cancer pain management (CPM) and describe their perceived barriers to CPM at oncology units. A descriptive cross-sectional design was utilized to obtain dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
5
35
2
Order By: Relevance
“…A similar situation of poor knowledge relating to chronic pain management and the use of analgesics among medical residents was also reported by a recent study conducted in Iran [31]. However, these results indicate a deeper knowledge gap compared to more recent studies conducted in Korea [5] and Jordan [32]. Addressing such knowledge problem among physicians can benefit from the experiences of other countries where similar problems were recognized and improved upon.…”
Section: Discussionsupporting
confidence: 76%
“…A similar situation of poor knowledge relating to chronic pain management and the use of analgesics among medical residents was also reported by a recent study conducted in Iran [31]. However, these results indicate a deeper knowledge gap compared to more recent studies conducted in Korea [5] and Jordan [32]. Addressing such knowledge problem among physicians can benefit from the experiences of other countries where similar problems were recognized and improved upon.…”
Section: Discussionsupporting
confidence: 76%
“…The barriers most commonly cited by professionals [11,22,28,44,48,59,98,100], patients and their caregivers [20,55,57,95] and the general public [51] were the fear of poor tolerance, side effects of opioids and drug addiction. However, the most common barriers cited by professionals were contrary to other similar studies, which have suggested that the most important barriers were poor assessment of pain and its management, patient reluctance to take opioids and inadequate staff knowledge of CPM [14,22,27,32,34,44,45,104]. Furthermore, a previous systematic review by Jacobsen et al [42] showed that physicians from countries, such as some states in the USA, Australia and Denmark were more often prescribing strong opioids in efficient doses, as they were less concerned about opioid addiction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting outcome was that several studies showed physicians had a better level of attitudes and knowledge towards CPM than nurses [22,32,44,45]. There was also a difference between oncologists and surgeons regarding their level of knowledge about cancer pain and its management [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations